The effect of Tinospora crispa on elevated blood glucose in streptozotocin induced diabetic rats - Firdausa, Sarah; Cho, Maung Maung; Khin, Maung Maung; Aung, Nilar; Ku Zaifah, Norsidah (2012)
Diabetes is a worldwide chronic metabolic disorder which can lead to poor quality of live and even death. Nowadays, herbal therapy is considered as an alternative therapy for diabetes. This study aimed to investigate the effect of Tinospora crispa aqueous extract (TCA) on elevated blood glucose in streptozotocin-induced diabetic rats. Diabetes mellitus was induced in Sprague-Dawley rats with streptozotocin (STZ) (50 mg/kg). The rats were divided into five groups (n=6), as follows : normal control(N), normal TCA treated(NT), diabetic control(D), diabetic TCA treated(DT), and diabetic treated with standard commercialized Vitamin E(DE) respectively. Intervention was given for four weeks and blood sample were withdrawn for measurement of fasting blood glucose. The data between groups were compared using one way ANOVA test, while paired T test was used to analyze those before and after treatment. Diabetic rats showed a significant increase in the blood glucose level after STZ induction (16.38+-0.54 mmol/dl) compared to the normal rats (4.98+-0.03mmol/dl;P<0.05). This elevated blood glucose remained steady till the end of study for group D and DE. The administration of TCA in DT group reduced the elevated levels of blood glucose in the 2nd,3rd and 4th weeks post-treatment considerable (P<0.05). In normal groups, there were no significant different between group N and NT before and after TCA administration. The body weight normally rose in normal groups compare to diabetic groups which slowly increased. In D and DE groups, the body weight decreased continuously started from the second week till the end of experiment. This study shows that Tinospora crispa aqueous extract may decrease elevated blood glucose level in streptozotocin induced diabetic rats and affect the body weight.